Optimized Resonance Control in Gold T-shaped Nanoantennas for Advanced Plasmonic Applications - Mahmud, Tanjoy; Ekra, Md Emadur Rahman; Ahmed, Tanvir; Bachar, Dipayon; Mahmud, Tonmoy (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2027)
Nanoscale resonant optical antennas are highly regarded for their capacity to enhance electric fields in localized volumes smaller than the diffraction limit. This makes them particularly attractive for coupling with quantum emitters. However, a significant challenge in applications involving spectral shifts is fabricate nanoantennas that provide two distinct resonances—one at the excitation frequency and another at the emission frequency. To address this, we propose a coupled T-shaped nanoantenna design that allows for independent control of the resonances, while sharing a common electromagnetic hot spot within the antenna gap. We present the fabrication of such structures and evaluate their spatial, time-integrated, spectral, and polarization-dependent electromagnetic field characteristics, both experimentally and theoretically. The nanoantennas display two separate resonances, each with distinct spectral and polarization behaviors. These resonance wavelengths can be independently adjusted by changing the geometry of the individual T-shaped antennas.